An experimental investigation on shape memory polymer and metallic stents under bending and radial compression. (21st October 2020) - Ansari, Mehdi; Golzar, Mohammad; Baghani, Mostafa; Taghavimehr, Mehrnoosh; Abbasi Shirsavar, Mehran; Yahyavi, Mahsa
Abstract: In this paper, shape memory polymers (SMPs) are fabricated by blending Polyurethane (PU) and Polycaprolactone (PCL). A novel method is used to make tubular stents using this blend. The solution coating method is applied to fabricate the SMP stent samples with a non-groove structure. Some metallic commercial stents made of the platinum-chromium alloy are used to compare SMP stents' the mechanical properties with metal ones. According to the stents' functionality, two mechanical tests, i.e., radial compression and three-point bending, are conducted in a range of body temperature. According to the mechanical test results, the tubular polymer stent shows a lower strength under the radial forces and a higher strength under the bending forces than to their metal counterparts. However, the mechanical properties of the SMP stents are in the range of metal stents. Thus, the PU/PCL SMP blend can be a promising candidate to be used as the coronary artery stents.